ORIGIN AND MEANING OF THE CONCEPT OF FRANCOPHONIE (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
In this paper, we first give a brief history of the emergence of the concept of Francophonie, then its definition or meaning, change and adaptation to the needs of the new modern time and new life circumstances. Initially connected by the common use of the French language in communication, the Francophone countries have been expanding their activities to various areas of human activity in recent decades. We point out, first of all, the necessity for the French language to develop today, adapting to the linguistic and cultural tradition and the peculiarities of numerous Francophone countries on five continents. We also present the main stages in the development of the idea of ​​Francophonie, as well as some of the most important official state and non-governmental international Francophone organizations.
Keywords: francophonie, French language, language space, cultural space, political-economic space